On the effect of foreign aid on corruption - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
The Okada & Samreth(2012, EL) finding that aid deters corruption could have an important influence on policy and academic debates. This paper partially negates their criticism of the mainstream approach to the aid-development nexus. Using updated data(1996-2010) from 52 African countries we provide robust evidence of a positive aid-corruption nexus. Development assistance fuels(mitigates) corruption(the control of corruption) in the African continent. As a policy implication, the Okada & Samreth(2012, EL) finding for developing countries may not be relevant for Africa.
Keywords: B20; F35; F50; O10; O55; 330; Foreign Aid; Political Economy; Development; Africa